Biomineral additives for self-healing of concrete - T. N. Chernykh; K. A. Gorbachevskykh; M. V. Kriushin; A. A. Orlov; M. V. Komelkova; P. O. Platkovskii (Vestnik MGSU)
Introduction. The reasons for the reduction of durability of flexural structures due to the violation of the protective layer of reinforcement are considered. It breaks down when cracks form. Cracks can self-heal by various methods, the most effective of which is microbial-induced precipitation of calcium carbonate.Materials and methods. Bacillus subtilis strains VKM B-70 and VKM B-501 (All-Russian Collection of Microorganisms), microsilica, metakaolin, and fly ash were used. Bacterial activity was assessed by culturing bacterial strains from tablet specimens. The pH of the specimens was determined using the pH meter. The crack growth rate was assessed by visual inspection of the tablet specimens by the optical microscope.Results. The results of the experiment on selection of optimal size of alginate bacterial granules for biomineral additives are shown. The effect of biomineral additives of various compositions on the overgrowth of cracks with a width of 100 to 500 µm was studied. The effect of increasing bacterial activity in the presence of the pozzolanic component is shown. The relationship between the alkalinity of the specimen medium and bacterial activity was revealed.Conclusions. The recommended granule diameter is 1–1.8 mm. The bacterial activity in such granules increases in the presence of pozzolanic component in the composition of the additive. Fly ash was most effective in formulations with Bacillus subtilus bacteria due to its ability to lower the pH of cement-sand compositions. By lowering the pH, conditions that are more favourable are created for the vital activity of bacteria. When using complex biomineral additives, there is a significant increase in the rate of crack healing, which will allow self-healing of cracks with a width of 100 microns in just five water-air cycles.